Aplicações da teoria dos grafos à teoria dos grupos - Oliveira, Marcelo Mendes de (2008)
This report deals with applications of Graph Theory to Group Theory. Once we construct the graph associated to a finite group, we get several interesting results on the group structure by analysing its associated graph with the help of various standard graph-theoretic tools. More precisely, the chromatic and independence numbers of the graph of a finite group allows us to estimate the maximal cardinality of an abelian subgroup of it, as well as the minimal size of a subset of the group, all of whose elements don’t commute in pairs; for finite abelian groups, we also study their free-sum subsets.